Policy learning in Norwegian school reform: a social network analysis of the 2020 incremental reform - Chanwoong Baek; Bernadette Hörmann; Berit Karseth; Oren Pizmony-Levy; Kirsten Sivesind; Gita Steiner-Khamsi (Taylor & Francis Group, 2018)
This policy study examines how policymakers and policy experts in Norway made us of research and studies - produced in Norway, in the Nordic countries and outside the Nordic region - to explain the 2020 incremental school reform. In total, 2 White Papers, 12 Green Papers and 3438 texts, cited in the White and Green Papers, were used as data for the text-based social network analysis. The three major findings were the following: First, the policymakers and experts make excessive use of references (on average, 246 references per White or Green Paper). The publications they cite are highly specialized and issue centred with little overlap between the various papers. Second, the policy references for the 2020 reform were mainly domestic. Approximately 70% of the referenced texts were published in Norway. Finally, the social network analysis enabled the authors to identify five texts that were influential and that bridged curriculum with quality monitoring reform topics. The authors suggest that more attention should be paid to an analysis of incremental reforms such as the 2020 reform in Norway. They identify a few of the blind spots that the more commonly used focus on fundamental reforms tends to produce.